STRATEGI KOMUNIKASI DAKWAH PENYULUH AGAMA ISLAM DALAM PEMBINAAN KELUARGA SAKINAH - Nurul Laila Hidayat (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2020)
The extension agents of islamic religious have an important role in implementing Islamic guidance in the midst of the dynamics of development of Indonesian society. An Islamic Religious Instructor is someone who is given the full duties and responsibilities, authority and rights under the auspices of the Ministry of Religion to carry out religious guidance and development to the community through the language of Religion. This study was qualitative with the type of case study, and data collection was carried out by interview, observation, and documentation methods, all of which were to answer problems regarding the communication model of Islamic religious extension agents in Sakinah village, Jember Regency. The informants of this study were the Head of KUA Tanggul District, Functional Islamic Religious Instructors, Honorary Islamic Religious Instructors, stakeholders, and the people of Sakinah Tanggul Kulon Village, Tanggul District, Jember Regency. The result of this study was analyzing the needs of Kampung Kamaran, Determining the Priority Scale for Sakinah Village coaching, Gradual and comprehensive coordination of all parties, Assistance for residents who do not have a marriage certificate, Creating an Islamic environment and Implementing Islamic Religious Education in Sakinah Village. Meanwhile, the response of the society in Sakinah Village to the da'wah of Islamic Religious Instructors in coaching the Sakinah family can be divided into negative responses and positive responses.